Influence of Teacher Characteristics on Academic Performance of Learners with Hearing Impairment in KCPE in Special Primary Schools in Selected Counties, Kenya. - Kering, Julius K.; Rop, Naftali K.; Ogola, Fredrick O. (My University, 2019)
This study explored the relationships between selected teacher characteristics and academic performance of learners with hearing impairment in Kenya Certificate of Primary Education (KCPE) in special primary schools in selected counties. The study used the descriptive survey research design. The selected teacher characteristics for the study included teacher level of qualification, teacher years of professional experience, teacher absenteeism from school and teacher pedagogical knowledge. One hundred and eight respondents were purposively selected for the study. This sample was made up of seventy one learners, thirty three teachers teaching upper primary and four head teachers. Data collected were categorized, coded and keyed into the computer software the Statistical Package for Social Science so as to get frequency tables and percentages. The findings showed majority of teachers handling learners with hearing impairment in special primary schools were highly qualified, experienced, attend school regularly and had the requisite pedagogical knowledge to cater for these learners effectively. Contrary to the findings, academic performance of learners with hearing impairment in KCPE in special primary schools continues to remain below average with most schools managing a mean of less than hundred and fifty marks. The study recommended capacity building for teachers through workshops and seminars on new skills and trends of effective handling of these learners. Also, curriculum support services and monitoring of instruction processes be enhanced by field officers and strengthening internal supervision of the school instruction processes
Keywords: Qualification; Professional Experience; Absenteeism; Pedagogical Knowledge; Academic Performance; KCPE; Special Schools